A theory of family employee involvement during resource paucity. Issue 3 (September 2016) - Lee, Soo-Hoon; Phan, Phillip H.; Ding, Hung-bin
Abstract: All organizations experience resource paucity at some point in their life-cycles. In this paper, we derive a human resource theory of family employee involvement in the family enterprise when it experiences resource paucity. We use a combination of social identity and stewardship theories to explain why family employees provide a competitive advantage to the family enterprise in such situations. Our paper contributes to ongoing theory development in familiness by showing that family identification and stewardship behaviors during resource paucity differentiate family and non-family employees. These differences explain the higher odds of survival among family enterprises facing resource paucity compared to non-family ones.